Retinoid Receptors in Bone and Their Role in Bone Remodeling - Henning, Petra; Conaway, H. Herschel; Lerner, Ulf H. (Frontiers in Endocrinology, 2015)
Vitamin A (retinol) is a necessary and important constituent of the body which is provided by food intake of retinyl esters and carotenoids. Vitamin A is known best for being important for vision, but in addition to the eye, vitamin A is necessary in numerous other organs in the body, including the skeleton. Vitamin A is converted to an active compound, all-trans-retinoic acid (ATRA), which is responsible for most of its biological actions. ATRA binds to intracellular nuclear receptors called retinoic acid receptors (RAR, RAR, RAR). RARs and closely related retinoid X receptors (RXR, RXR, RXR) form heterodimers which bind to DNA and function as ligand activated transcription factors. It has been known for many years that hypervitaminosis A promotes skeleton fragility by increasing osteoclast formation and decreasing cortical bone mass. Some epidemiological studies have suggested that increased intake of vitamin A and increased serum levels of retinoids may decrease bone mineral density and increase fracture rate, but the literature on this is not conclusive. The current review summarizes how vitamin A is taken up by the intestine, metabolized, stored in the liver and processed to ATRA. ATRA’s effects on formation and activity of osteoclasts and osteoblasts are outlined, and a summary of clinical data pertaining to vitamin A and bone is presented.